2010
DOI: 10.1021/ja908560n
|View full text |Cite
|
Sign up to set email alerts
|

Tuning Supramolecular Rigidity of Peptide Fibers through Molecular Structure

Abstract: We synthesized a series of peptide amphiphiles (PAs) with systematically modified amino acid sequences to control the mechanical properties of the nanofiber gels they form by self-assembly. By manipulating the number and position of valines and alanines in the peptide sequence we found that valines increase the stiffness of the gel while additional alanines decrease the mechanical properties. Vitreous ice cryo-transmission electron microscopy shows that all PA molecules investigated here form nanofibers 8–10 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

34
478
2
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 374 publications
(517 citation statements)
references
References 49 publications
(115 reference statements)
34
478
2
3
Order By: Relevance
“…Comparing IDIDI (1 wt %) and D2I3 (2 wt %) hydrogels, the G′ value increased by two orders of magnitude from 2 to 200 kPa, respectively. These stiffness values are in the region of many soft tissues and compare well to previously published peptide hydrogel systems, including aromatic peptides4, 17 and peptide–amphiphile hydrogels 27, 28. The ability to tune the G′ value across a large range holds great promise for applications in tissue engineering, given that the behavior of cells has been found to be heavily influenced by the mechanical properties of their surrounding environment 29, 30…”
supporting
confidence: 79%
See 4 more Smart Citations
“…Comparing IDIDI (1 wt %) and D2I3 (2 wt %) hydrogels, the G′ value increased by two orders of magnitude from 2 to 200 kPa, respectively. These stiffness values are in the region of many soft tissues and compare well to previously published peptide hydrogel systems, including aromatic peptides4, 17 and peptide–amphiphile hydrogels 27, 28. The ability to tune the G′ value across a large range holds great promise for applications in tissue engineering, given that the behavior of cells has been found to be heavily influenced by the mechanical properties of their surrounding environment 29, 30…”
supporting
confidence: 79%
“…However, at 2 wt % the D2I3 sequence was significantly stiffer and had the greatest red‐shift in the CD spectra at this concentration (Figure 3 A,B). Previous studies have suggested that a red‐shift in the CD spectra of β‐sheets is representative of more twisted and distorted arrangements 28, 36, 37. The degree of twisting of β‐sheets is centered around the middle of the sequence 34.…”
mentioning
confidence: 96%
See 3 more Smart Citations